Comparative Language Style of Moses Story in Al-Quran - Romdani; Yumna Rasyid; Aceng Rahmat (ALSINATUNA, 2018)
The purpose of the study is to find the comparative language style of Moses Story in AlQuran. Then, the people knew the context meaning of the story to implement in the real life. The research method is qualitative using content analysis. The data used in this study are the verses of Al-Quran. To determine the validity of data, there are analysis of credibility, transferability, dependability, and conformability. As another data source, the author uses references to literary theory related to the style of language. The instrument of this research is the researcher itself according to qualitative research characteristic. Comparative language styles contained in the verses of the story of Moses in the AL-Quran include; 1) Personification language style has 3 cases, 2) allegorical language style has 5 cases, 3) periphrasis language style has 5 cases, 4) similar language style has 4 cases, 5) hyperbolic language style has 5 cases, 6) metaphoric language style has 6 cases, 7) litotes language style has 3 cases, 8) allusion language style has 11 cases, and 9) synecdoche language style has 3 cases. The commonly used language style comparison is the allusion to language style.